PERSONALITY-ORIENTED TASK DEVELOPMENT IN ENGLISH LANGUAGE EDUCATION: METHODOLOGICAL GUIDELINES AND EFFECTIVE PRACTICES - Djurakulova , Diyora (Scientific practical conference, 2025)
This article analyzes methodological strategies for the incorporation of learner-centered tasks in English language education, particularly in higher education establishments. The study examines essential elements of a personality-oriented approach, such as autonomy, active participation, and collaborative learning. Task design, instructor facilitation, and the development of authentic, relevant learning activities that effectively meet real-world communication needs are of paramount importance.